The Impact of Job Satisfaction and Non-Financial Compensation on Employee Performance at PDAM Tirta Deli Kabupaten Deli Serdang - Akmal; Marzuki; Afrizal; Chaidir; Dedi Sufriadi (Universitas Serambi Mekkah, 2024)
The assessment of employee performance plays a crucial role in shaping policies and decisions related to human resources within a company. Factors influencing employee performance include job satisfaction and the provision of non-financial compensation. This study aims to investigate the influence of job satisfaction and non-financial compensation on employee performance at PDAM Tirta Deli in Deli Serdang Regency. The research adopts an associative type, seeking to explore the impact of job satisfaction (X1) and non-financial compensation (X2) on employee performance (Y) at PDAM Tirta Deli, Deli Serdang Regency. Data collection techniques involve observation, questionnaires, and literature review, utilizing a Likert-scale questionnaire as the instrument. The population comprises all employees at PDAM Tirta Deli, Deli Serdang Regency, totaling 164 individuals, including 93 permanent and contractual employees and 71 contract-based employees. The sample for this study consists of 93 permanent and contractual employees at PDAM Tirta Deli, Deli Serdang Regency. The results indicate a significant impact of job satisfaction and non-financial compensation on employee performance at PDAM Tirta Deli, Deli Serdang Regency. The researchers recommend that PDAM Tirta Deli continues to enhance employee job satisfaction and provides effective non-financial compensation to stimulate optimal employee performance.